The 67 kDa laminin receptor: structure, function and role in disease. Issue 1 (12th February 2008) - Nelson, John; McFerran, Neil V.; Pivato, Géraldine; Chambers, Emma; Doherty, Caroline; Steele, David; Timson, David J.
Abstract : The 67LR (67 kDa laminin receptor) is a cell-surface receptor with high affinity for its primary ligand. Its role as a laminin receptor makes it an important molecule both in cell adhesion to the basement membrane and in signalling transduction following this binding event. The protein also plays critical roles in the metastasis of tumour cells. Isolation of the protein from either normal or cancerous cells results in a product with an approx. molecular mass of 67 kDa. This protein is believed to be derived from a smaller precursor, the 37LRP (37 kDa laminin receptor precursor). However, the precise mechanism by which cytoplasmic 37LRP becomes cell-membrane-embedded 67LR is unclear. The process may involve post-translational fatty acylation of the protein combined with either homo- or hetero-dimerization, possibly with a galectin-3-epitope-containing partner. Furthermore, it has become clear that acting as a receptor for laminin is not the only function of this protein. 67LR also acts as a receptor for viruses, such as Sindbis virus and dengue virus, and is involved with internalization of the prion protein. Interestingly, unmodified 37LRP is a ribosomal component and homologues of this protein are found in all five kingdoms. In addition, it appears to be strongly associated with histones in the eukaryotic cell nucleus, although the precise role of these interactions is not clear. Here we review the current understanding of the structure and function of this molecule, as well as highlighting areas requiring further research.